Factors Associated with The Incidence of Pulmonary Tuberculosis in Lebak District, Banten Province, Indonesia - Lubis, Rosmawaty; Hisni, Dayan; Rahmatullah, Bobby Rizky (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2023)
Introduction: Pulmonary tuberculosis (TB) is a chronic disease caused by Mycobacterium tuberculosis. The prevalence of pulmonary TB is increasing every year. The previous studies found that knowledge, physical condition of the house, gender and education level are the well-known of factors associated with the TB cases. This study aims to determine the factors associated with the incidence of Pulmonary TB at Puskesmas Maja, Lebak Regency, Banten Province, Indonesia.Methods: Case control study design was used in this study. Total 20 cases and controls were recruited. Cases are individuals aged over 15 years with pulmonary tuberculosis who were confirmed by sputum examination with acid-fast staining (BTA+) showing the presence of Mycobacterium tuberculosis. Controls were individuals with negative sputum examination results. A purposive sampling technique was used to find the defined-case and control groups. A study questionnaire was used to collect the determinant factors and house condition parameter was measured directly. The chi-square test was used to determine the association of each variable related to TB incidence.Results: The demographic data showed that the majority of TB patients in Puskesmas Maja were male who had an elementary to high school education level and had a low level of knowledge and unhealthy physical conditions of the house. The results of bivariate analysis showed that there was a significant relationship between gender, education level, knowledge, and physical condition of the house with the incidence of pulmonary TB at Puskesmas Maja, Lebak Regency.Conclusion: This study concludes that all four variables have a significant relationship with the occurrence of Pulmonary TB at Puskesmas Maja, Lebak Regency. The results of this study can be a source of reference for further research and also become the basis for overcoming pulmonary TB in Banten Province in particular and in Indonesia